Cytokine production, glutamate release and cell death in rat cultured astrocytes treated with unconjugated bilirubin and LPS - Fernandes, A (2015)
In hyperbilirubinemic newborns, sepsis is considered a risk factor for kernicterus. Evidence shows that injury to astrocytes triggers cytokine release. We examined the effects of unconjugated bilirubin (UCB) alone, or in combination with LPS, on the relea